Novel Biophotonics Techniques and Applications V 2019
DOI: 10.1117/12.2526778
|View full text |Cite
|
Sign up to set email alerts
|

Influence of interaction time on the red blood cell (dis)aggregation dynamics in vitro studied by optical tweezers

Abstract: Optical tweezers (OT) is a unique Nobel Prize winning technology that has been widely used in studying cell interaction dynamics at a single-cell level with highly accurate manipulating of living cells and the ability to detect ultra-low intercellular forces. The reversible aggregation process of red blood cells (RBCs) that strongly influences the blood rheological properties thus being critical for blood microcirculation has long been research studied. However, in spite of plentiful researches dealing with RB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 14 publications
2
10
0
Order By: Relevance
“…In studies of the characteristics of blood components and rheology at a single-cell level, the easy-to-implement and well-developed conventional dual-beam OTs are the most commonly used trapping geometry. In a typical dual-beam OTs system as shown in Figure 4 [73], by using polarizing beam splitters (PBS), one infrared laser beam is split into two polarization-based beams and focused by a large numerical aperture microscope objective. With beam positions being adjustable by rotating reflective mirrors or by moving the sample stage, two individual RBCs can be trapped and controlled simultaneously.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…In studies of the characteristics of blood components and rheology at a single-cell level, the easy-to-implement and well-developed conventional dual-beam OTs are the most commonly used trapping geometry. In a typical dual-beam OTs system as shown in Figure 4 [73], by using polarizing beam splitters (PBS), one infrared laser beam is split into two polarization-based beams and focused by a large numerical aperture microscope objective. With beam positions being adjustable by rotating reflective mirrors or by moving the sample stage, two individual RBCs can be trapped and controlled simultaneously.…”
Section: Methodsmentioning
confidence: 99%
“…With the double-beam OTs system as illustrated in Figure 4 and the above-stated methods, our group recently revealed the influence of cell interaction time (up to 300 s) on RBC disaggregation dynamics [73,102]. The results showed that the RBC disaggregation force increases with initial interaction time between two RBCs, whereas the aggregation force is independent to the cell contact time.…”
Section: Evaluation Of Dynamic Cell-cell Interaction Between Rbcsmentioning
confidence: 96%
See 3 more Smart Citations